2013
DOI: 10.1016/j.crohns.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Use of exclusive enteral nutrition in paediatric Crohn's disease in The Netherlands

Abstract: A six-week course of EEN is effective in newly diagnosed paediatric CD, with response rates that seem to be influenced by disease location and nutritional status, but not by type of formula. Non-adherence occurs frequently and limits the success of this treatment in everyday clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…Despite the convincing results regarding immediate benefits of nutritional treatment, duration of remission is poorly studied. In accordance with reports from other centres, [17][18][19] we observed relapses within 1 year in approximately two-thirds of patients following each course of EEN. The high relapse rate occurred in spite of early introduction of immunomodulatory therapy with azathioprine.…”
Section: Discussionsupporting
confidence: 76%
“…Despite the convincing results regarding immediate benefits of nutritional treatment, duration of remission is poorly studied. In accordance with reports from other centres, [17][18][19] we observed relapses within 1 year in approximately two-thirds of patients following each course of EEN. The high relapse rate occurred in spite of early introduction of immunomodulatory therapy with azathioprine.…”
Section: Discussionsupporting
confidence: 76%
“…The high proportion of female patients and secondary school age patients is likely to have affected treatment completion. Females and older adolescents are more likely to withdraw from treatment due to non-adherence [10] and this trend was observed in the current study, whereby 73% of adolescents did not complete EN treatment compared with only 26% of young adults aged 18 years and older. EN treatment may be a more acceptable treatment for patients who have finished secondary education and moved into the workforce or tertiary education.…”
Section: Discussionsupporting
confidence: 51%
“…Nutrition-based treatments, the most common being exclusive enteral nutrition (EEN), is recommended as a first-line therapy to treat active paediatric CD [5]. EEN is now commonly used to treat active CD in children and adolescents in New Zealand (NZ) [6], Australia [7], Asia [8], Canada [9] and Europe [10]. Adults with CD are interested in nutrition-based alternatives to corticosteroids [11], and EEN is regularly used in Japan [12], and increasingly in China [13] to treat adults with active CD.…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective study, Grogan et al18 reported that 93% and 79% of patients who received elemental formula and a polymeric diet, respectively, achieved remission after 6 weeks of EEN treatment. Furthermore, de Bie et al19 reported that EEN treatment with hyperosmolar sip feeds or a polymeric diet for 6 weeks resulted in complete remission in 55 of 77 patients (71%); however, EEN was discontinued in 10 of 77 patients (13%) due to nonadherence. The findings of the present study indicate similar efficacy with a shorter EEN treatment duration.…”
Section: Discussionmentioning
confidence: 99%